Kontribusi Koordinasi Mata Tangan Dan Kekuatan Otot Lengan Terhadap Kemampuan Pukulan Forehand Smash Permainan Bulutangkis - Suparman Suparman; Ikadarny Ikadarny; Dionisius Nahar; Nurjamal Nurjamal (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
The purpose of this study was to determine the contribution of eye-hand coordination and arm muscle strength to the forehand smash ability of the students of Penjaskesrek STKIP YPUP Makassar. This research is a correlative research with a quantitative approach. The population in this study were all students who had passed the badminton course with a total of 117 students. The sample taken in this study were 30 students obtained by simple random sampling technique. Data collection was carried out by measuring hand-eye coordination with a tennis ball throwing and catching test with a throw that hit the target and was caught by hand with the results of the first 10 throws and 10 second throws. Data was collected by measuring arm muscle strength using a push-up test which was carried out for 60 seconds. Test the ability to hit the forehand smash hitting 10 shuttlecocks towards the areas that have been given numbers. Analysis of research data was carried out as many as three statistical calculation tests, namely, descriptive test, prerequisite test and hypothesis testing. The prerequisite test used is the normality test. While the hypothesis test used is simple regression test and multiple regression test. The results of research data processing showed that eye-hand coordination contributed to the forehand smash ability by 37.8%. Arm muscle strength contributes to the forehand smash ability of 41.2%. Eye-hand coordination and arm muscle strength together contributed to the forehand smash ability of 62.2%.